2012
DOI: 10.1080/01419870.2011.594167
|View full text |Cite
|
Sign up to set email alerts
|

HIV and Latino migrant workers in the USA

Abstract: Migrant workers from Latin America are an essential source of economic development in the US agricultural industry. A majority of migrants are from Mexico and are undocumented and they represent a vulnerable and marginalized group in American society. There is a growing concern for HIV disease in the migrant community. The HIV prevalence rate among migrants is higher than the average rates in USA and in countries of Latin America. There are many behavioural, social, cultural, and health care risk factors and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 17 publications
0
19
1
Order By: Relevance
“…Compared with the results in the previous studies in the US [23], our survey participants reported more accurate knowledge of condoms (e.g., their effectiveness against pregnancy and HIV, and the fact that their use should not be restricted to sex with prostitutes and between men). Despite this knowledge, however, the actual condom use among our survey participants was as low as among participants in previous studies [12,[14][15][16][17][18][19]23]. Our study also found MFWs' beliefs and cultural barriers lead to their hesitation to use condoms (e.g., condoms are uncomfortable, ''Mexican men don't like to use condoms'').…”
Section: Needs and Risks At The Individual And Country Levelcontrasting
confidence: 79%
See 2 more Smart Citations
“…Compared with the results in the previous studies in the US [23], our survey participants reported more accurate knowledge of condoms (e.g., their effectiveness against pregnancy and HIV, and the fact that their use should not be restricted to sex with prostitutes and between men). Despite this knowledge, however, the actual condom use among our survey participants was as low as among participants in previous studies [12,[14][15][16][17][18][19]23]. Our study also found MFWs' beliefs and cultural barriers lead to their hesitation to use condoms (e.g., condoms are uncomfortable, ''Mexican men don't like to use condoms'').…”
Section: Needs and Risks At The Individual And Country Levelcontrasting
confidence: 79%
“…This overlaps with the findings of the previous Canadian study [2,4,20], although it is impossible to compare the ratios as we did not include these questions in our survey. A cause for concern is that focus group participants, like their counterparts in the United States, reported potentially risky behaviour, including sex with multiple partners, transactional sex [12,18], and sex between men, possibly in part as a result of the imbalance between male and female workers [3,12], as well as low and inconsistent condom use [12,[14][15][16]19]. Compared with the results in the previous studies in the US [23], our survey participants reported more accurate knowledge of condoms (e.g., their effectiveness against pregnancy and HIV, and the fact that their use should not be restricted to sex with prostitutes and between men).…”
Section: Needs and Risks At The Individual And Country Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies suggest that drug use is initiated in the U.S., while binge drinking, a more socially sanctioned behavior, is carried over from the country of origin (Alaniz, 2002; Borges et al, 2009; Davis and Winters, 2002; Hernández et al, 2004; Magis-Rodriguez et al, 2009; Mills et al, 2012; Persichino and Ibarra, 2012; Valdez et al, 2009; Worby and Organista, 2013). These studies suggest that the environment in the U.S. may play a role in increased substance use.…”
Section: Introductionmentioning
confidence: 99%
“…For many men in the study, HIV infection was detected after they had developed symptoms and, in some cases, were seriously ill. Emilio and the other participants described fear, stigma, fatalism, lack of knowledge, and lack of access as reasons that they did not test earlier, all of which are common barriers identified in the migrant health literature (Persichino and Ibarra 2012; Rhodes et al 2006; Rhodes and Hergenrather 2007). However, several, including Emilio, described ways that some aspects of their lives had improved after they finally were diagnosed and began receiving HIV care.…”
Section: Discussionmentioning
confidence: 99%